The Effect of Soft Soil Reinforcement Using Gravel Columns and Used Tire Columns in the Graha Lentera Holtekam Residential Area - Hendra Sakti Muslimin Ali Wandan; Duha Awaluddin Kurniatullah; Mujiati Mujiati; Bahtiar Bahtiar; Bernathius Julison (International Journal Labs, 2025)
The opening of new land to be used as a location for housing development (KPR) or Shop Houses (Ruko) as residential and business places that may technically not meet the requirements and standards for erecting a construction building in the area, let alone on a mass basis. Because the potential for construction failures is very prone to occur, such as land subsidence (Settlement). These factors must be found to increase the carrying capacity of the land so that it can meet the requirements to erect a construction building that is safe, economical and at the same time the life of the building can be longer. Based on the description mentioned above, the researcher is interested in modeling carried out in the engineering laboratory of Cenderawasih University with sakla 1; 50, this research was carried out there are three types, namely soil without reinforcement, soil with a 6 cm diameter gravel column reinforcement with a depth variation of 4 cm and 8 cm, and soil with a 6 cm diameter used tire column with a depth variation of 4 cm and 6 cm. This test is carried out by applying pressure or load in a vertical direction, The tool used is in the form of a hydraulic jack by paying attention to the load reading dial and the drop reading dial until the reading is fixed or the drop dial does not show any further decline. Based on the results of the analysis of this study, it was obtained that: The test was applied on soil without reinforcement obtaining an ultimate load of 950.00 kpa with a qijin of 380.00 kpa, soil with the reinforcement of gravel columns with the greatest carrying capacity of 1,849 Kpa with a qijin of 739.444 kN or producing a carrying capacity 95% greater than the soil without reinforcement.